The Potential Use of Wolbachia-Based Mosquito Biocontrol Strategies for Japanese Encephalitis. - Claire L Jeffries; Thomas Walker (Public Library of Science (PLoS), 2015)
Japanese encephalitis virus (JEV) is a zoonotic pathogen transmitted by the infectious bite of Culex mosquitoes. The virus causes the development of the disease Japanese encephalitis (JE) in a small proportion of those infected, predominantly affecting children in eastern and southern Asia. Annual JE incidence estimates range from 50,000-175,000, with 25%-30% of cases resulting in mortality. It is estimated that 3 billion people live in countries in which JEV is endemic. The virus exists in an enzootic transmission cycle, with mosquitoes transmitting JEV between birds as reservoir hosts and pigs as amplifying hosts. Zoonotic infection occurs as a result of spillover events from the main transmission cycle. The reservoir avian hosts include cattle egrets, pond herons, and other species of water birds belonging to the family Ardeidae. Irrigated rice fields provide an ideal breeding ground for mosquitoes and attract migratory birds, maintaining the transmission of JEV. Although multiple vaccines have been developed for JEV, they are expensive and require multiple doses to maintain efficacy and immunity. As humans are a "dead-end" host for the virus, vaccination of the human population is unlikely to result in eradication. Therefore, vector control of the principal mosquito vector, Culex tritaeniorhynchus, represents a more promising strategy for reducing transmission. Current vector control strategies include intermittent irrigation of rice fields and space spraying of insecticides during outbreaks. However, Cx. Tritaeniorhynchus is subject to heavy exposure to pesticides in rice fields, and as a result, insecticide resistance has developed. In recent years, significant advancements have been made in the potential use of the bacterial endosymbiont Wolbachia for mosquito biocontrol. The successful transinfection of Wolbachia strains from Drosophila flies to Aedes (Stegomyia) mosquitoes has resulted in the generation of "dengue-refractory" mosquito lines. The successful establishment of Wolbachia in wild Aedes aegypti populations has recently been demonstrated, and open releases in dengue-endemic countries are ongoing. This review outlines the current control methods for JEV in addition to highlighting the potential use of Wolbachia-based biocontrol strategies to impact transmission. JEV and dengue virus are both members of the Flavivirus genus, and the successful establishment of Drosophila Wolbachia strains in Cx. Tritaeniorhynchus, as the principal vector of JEV, is predicted to significantly impact JEV transmission.